Clinical prognostic factors in canine histiocytic sarcoma1. (23rd June 2016) - Dervisis, N. G.; Kiupel, M.; Qin, Q.; Cesario, L.
Abstract: Canine histiocytic sarcoma (HS) is an aggressive neoplasia with variable clinical course and fatal outcome. The goals of this study were to evaluate a large cohort of canine patients with immunohistochemically confirmed HS and identify clinical prognostic factors. Biopsy submissions to the Michigan State University with tentative HS diagnoses were histologically and immunohistochemically confirmed, medical records collected, and interviews with relevant veterinary clinics conducted. Of 1391 histopathology submissions with a diagnosis containing the word 'histiocytic', 335 were suspicious for malignancy, and 180 were consistent with HS and had adequate clinical information recorded. The most commonly represented breeds were Bernese mountain dogs ( n  = 53), labrador retrievers ( n  = 26) and golden retrievers ( n  = 17). Median survival for all dogs in the study was 170 days, and subgroup analysis identified palliative treatment, disseminated HS, and concurrent use of corticosteroids as statistically significant negative factors for survival, in both uni‐ and multi‐variate methodologies.